Kebangkitan Yesus: Analisis Naratif Injil Lukas 23:56-24:12 - Herianto, Tjatur (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2019)
The Scriptures are the main guidelines in the Christians’ life of faith. The significance of this role has stimulated various interpretation methods of the Scriptures that are oriented to help the faithful find meanings relevant to their lives. Narrative analysis is one of the methods that are developed to reach fuller understandings and to communicate the biblical messages to a wider context of readers. It pays greater attention to the forms of personal stories and witnesses, which are typical of the Scriptures as well as of human communication model. Doing narrative analysis to the scriptural texts refers to the same elements and techniques as analysing narratives in general. This method explores the narrative elements of a scriptural text as a starting point for its further interpretation, that is, towards imagining the narrator and his or her viewpoints, the characterisation, the plot, the setting (concerning time and place), and the storytelling style. This article examines the resurrection narrative of Jesus Christ in Luke 23:56-24:12 by revealing its previously mentioned narrative elements and offering day-to-day inspirations that might be beneficial to the Christians.